2009
DOI: 10.1002/jbm.a.32626
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan‐based scaffold for in vivo regeneration of the rat vena cava: Preliminary results in an animal model

Abstract: The aim of this study was to develop a prosthetic graft that could perform as a small-diameter vascular conduit for vein regeneration. The difficulty of obtaining significant long-term patency and good wall mechanical strength in vivo has been a significant obstacle in achieving small-diameter vein prostheses. Fifteen Male Wistar rats weighing 250-350 g were used. Tubular structures of hyaluronan (HYAFF-11 tubules, 2 mm diameter, and 1.5 cm length) were implanted in the vena cava of rats as temporary absorbabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…18,28,29 In a previous study, we confirmed that a PLCL scaffold has similar compliance to native arteries that of its PTFE counterpart. 4,36,37 The vascular grafts degraded appropriately so as to maintain the blood pressure and induce regeneration over time as shown in Table 1. 30 In vascular surgery, expanded PTFE or Dacron is usually used clinically; however, these synthetic materials do not degrade in the body.…”
Section: Discussionmentioning
confidence: 99%
“…18,28,29 In a previous study, we confirmed that a PLCL scaffold has similar compliance to native arteries that of its PTFE counterpart. 4,36,37 The vascular grafts degraded appropriately so as to maintain the blood pressure and induce regeneration over time as shown in Table 1. 30 In vascular surgery, expanded PTFE or Dacron is usually used clinically; however, these synthetic materials do not degrade in the body.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, human vascular cells, such as endothelial cells (62) and smooth muscle cells (SMCs) (63), were grown in vitro on benzylic esters of hyaluronic acid (namely HYAFF-11 biomaterials) constructs to develop new tissue-engineered vascular substitutes. Previous in vivo studies (65)(66)(67)(68) confirmed that HYAFF tubes could sequentially orchestrate the vascular regeneration events needed for very small artery reconstruction. HYAFF-11 was shown to be very well tolerated and to elicit no adverse reactions in clinical practice (62,63,69).…”
Section: Hyaluronic Acid Scaffoldsmentioning
confidence: 90%
“…They may also overcome problems related to current vascular implant materials that insufficiently recruit endothelial cells to form a normally functional and confluent endothelium, a key challenge to reinstating vascular homeostasis at the surgical site. An Italian team obtained stimulating results in testing vascular prostheses entirely made of HA in rat and pig experimental models (65)(66)(67)(68). In this case, human vascular cells, such as endothelial cells (62) and smooth muscle cells (SMCs) (63), were grown in vitro on benzylic esters of hyaluronic acid (namely HYAFF-11 biomaterials) constructs to develop new tissue-engineered vascular substitutes.…”
Section: Hyaluronic Acid Scaffoldsmentioning
confidence: 99%
“…To overcome this limitation, HA is cross-linked with ethyl esters, benzyl esters, or other biodegradable polymers to enhance the mechanical properties while retaining excellent biocompatibility [368,369]. Such HA hydrogels are extremely versatile and can be fabricated into sheets, membranes, sponges, tubes, fibers, and scaffolds for wound healing [370], regeneration of the trachea [371], cartilage [372], vasculature [373], and nerve tissues [374]. HA is also available in the form of nanoparticles to deliver chemotherapeutics and other drugs [375,376].…”
Section: Proteins and Poly(amino Acids)mentioning
confidence: 99%